Climate factors determine the utilization strategy of forest plant resources at large scales - Wang, Jiangfeng; Wang, Xianxian; Ji, Yuhui; Gao, Jie (Frontiers in Plant Science, 2022)
Plant functional traits are a representation of plant resource utilization strategies. Plants with higher specific leaf area (SLA) and lower leaf dry matter content (LDMC) exhibit faster investment-return resource utilization strategies. However, the distribution patterns and driving factors of plant resource utilization strategies at the macroscale are rarely studied. We investigated the relative importance of climatic and soil factors in shaping plant resource utilization strategies at different life forms in forests using data collected from 926 plots across 163 forests in China. SLA and LDMC of plants at different life forms (i.e., trees, shrubs, and herbs) differ significantly. Resource utilization strategies show significant geographical differences, with vegetation in the western arid regions adopting a slower investment-return survival strategy and vegetation in warmer and wetter areas adopting a faster investment-return survival strategy. SLA decreases significantly with increased temperature and reduced rainfall, and vegetation growing in these conditions exhibits conservative resource utilization. Mean annual precipitation (MAP) is a key climatic factor that controls the resource utilization strategies of plants at the macroscale. Plants use resources more conservatively as soil pH increases. The influence of climate and soil factors is coupled to determine the resource utilization strategies of plants occupying different life forms at the macroscale, but the relative contribution of each varies across life forms. Our findings provide a theoretical framework for understanding the potential impact of increasing global temperatures on plant resource utilization.